Effects of different rates of propofol with or without S-ketamine on ventricular function in healthy cats – a randomized study - Marangoni, Sabrine; Ubiali, Matheus; Ambrosini, Francieli; Jahnel, Larissa; Vilani, Julia M.; Steagall, Paulo V.; Vilani, Ricardo Guilherme D’Otaviano de Castro (Frontiers in Veterinary Science, 2023)
Propofol is used for anesthetic induction in cats and for procedural sedation in countries where alfaxalone is not available. Studies have reported propofol-related effects in echocardiography variables in dogs and humans. However, there is a lack of echocardiography studies investigating propofol-related effects in cats. This study aimed to use echocardiography to investigate echocardiographic changes of three protocols using propofol: propofol-slow (2 mg/kg/min; PS); propofol-fast (8 mg/kg/min; PF); propofol-ketamine (S-ketamine 2 mg/kg bolus followed by propofol 2 mg/kg/min; PK) in healthy premedicated (gabapentin-buprenorphine-acepromazine; 200 mg/cat, 0.4 and 0.1 mg/kg, respectively), non-intubated cats. Echocardiographic measurements were obtained at three time points: baseline (before the administration of propofol), end of propofol titration (end-point, T0), and 15 minutes after T0 (T15). Propofol at a lower rate continued from T0 to T15. Echocardiographic and physiological variables included fractional shortening (FS%), ejection fraction (EF%), HR, BP and others. Propofol requirements at T0 for PF, PS and PK groups were 5.0 ± 0.9, 3.8 ± 0.7 and 2.4 ± 0.5 mg/kg, respectively. EF% did not changed over time nor between groups. PF and PK showed a reduction in FS% at T0 (47 ± 6 to 34 ± 6 and 42 ± 6 to 36 ± 5, respectively). BP reduced significantly in groups PF and PS (136 ± 26 to 105 ± 13 and 137 ± 22 to 115 ± 15 mmHg, respectively). It is unclear whether changes in echocardiography variables were of clinical relevance related to treatment groups or a result of within-group individual responses.